PROSPECTS FOR QUANTIFYING ENVIRONMENTAL INDICATORS FOR THE GENERATION, TRANSPORTATION, SORTING, RECYCLING, SERVICING AND EFFICIENT USE OF LANDFILLS OF CONSTRUCTION WASTE (British Journal of Global Ecology and Sustainable Development, 2025)
It is time to scientifically establish the use of electronic digitization services for the exchange of information on the cost of environmental and sanitary-epidemiological operations, the level of service coverage, recycling, extension of the life of landfills, and the cost of environmental and sanitary-epidemiological operations in construction waste management using effective environmental indicators.